Effective use of a vessel‐sealing system for laparoscopic unroofing of liver cysts. Issue 1 (February 2015) - Kanamoto, Mami; Imura, Satoru; Morine, Yuji; Utsunomiya, Tohru; Mori, Hiroki; Arakawa, Yusuke; Takasu, Chie; Shimada, Mitsuo
Abstract Introduction Liver cysts that present with symptoms such as jaundice, abdominal pain, and intra‐cystic infection require treatment. In laparoscopic unroofing of liver cysts, appropriate treatment is needed in cases where the cystic walls contain vessels or bile ducts. A vessel‐sealing system can seal not only vessels, but also bile ducts. We experienced four cases in which laparoscopic unroofing of liver cysts was performed with a vessel‐sealing system. Materials and Surgical Technique Case 1 was a woman in her 70s who presented at our hospital with abdominal pressure. Abdominal CT showed liver cysts with a maximum diameter of 13 cm. Laparoscopic unroofing was performed with LigaSure Impact. Case 2 was a woman in her 50s with abdominal discomfort. CT showed a cyst 15 cm in diameter situated in the right lobe. We performed SILS using a LigaSure Blunt Tip to unroof the cyst. Case 3 was a man in his 80s with abdominal pain. CT showed a huge cyst 25 cm in diameter in the right lobe. We performed hybrid SILS with a LigaSure Blunt Tip to unroof the cysts. Case 4 was a woman in her 70s with upper abdominal pain. CT showed multiple cysts with a maximum diameter of 15 cm in the bilateral lobes. We performed hybrid SILS to successfully unroof her cysts. None of the cases experienced postoperative complications, such as bleeding or bile leakage, and none experienced recurrence of cysts. Discussion A laparoscopic unroofing using a vessel‐sealing system can be a minimally invasive and safe treatment for liver cysts.